Contusões e pH de carcaças de bovinos transportados por diferentes distâncias no verão e inverno - Morais, Hugo Ribeiro (2012)
The aim of the present study was to determine the influence of transport distance of cattle in winter and summer on pH 24 hours post mortem and occurrence of bruises. 420 cows were slaughtered in Uberlândia - MG and come from Triângulo Mineiro. The experimental design was completely randomized in a 2x2 factorial, with two distances (15-85 km and 140-200 km) and two seasons (summer and winter), with four replicates each, except trucks that traveled for 15-85 km in summer (nine replications). The research was developed in July 2011 and January 2012. The distance on unpaved roads in the route 15-85 km was 10-18 km (winter) and 4-10 km (summer). On the other side, in the route 140-200 km, the animals traveled for 13-30 km (winter) and 12-18 km (summer). The occurrence, location, amount and degree of recent lesions, and pH 24h were assessed. Quantitative variables were subjected to analysis of variance followed by medium test, while the qualitative ones were evaluated through chi-square test. The pH value of 5.908 in carcasses of cattle transported in winter was higher than in summer - 5.711, not varying in the measured distances. The frequency of injuries in animals transported in winter - 97.78% - was higher than in summer - 88.26%. 77.39% of them were injured in rear and 94.02% presented grade I. The amount of injuries ranged from 1.9 to 2.36 kg by injured carcass, with a total weight of 168.575 kg. There was a greater presence of bruising in cattle transported over greater distances - 97.45% - than in short distances - 85.95%. Cows transported by road for up to 200 km have no change in pH 24h, but longer distances cause more bruising, especially grade I in the rear. In winter, there is a higher frequency of injuries than in summer.